2023
DOI: 10.1145/3522713
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Hyperspectral Image Classification with Dual Hierarchical Learning

Abstract: Hyperspectral image (HSI) classification aims at predicting the pixel-wise labels in an image, where there are only a few labeled pixel samples (hard labels) for training. It is a challenging task since the classification process is susceptible to over-fitting under training with limited samples. To relieve this problem, we propose a method based on dual hierarchical learning. First, we employ a connectionist hyperspectral convolution (HC) network to capture the representations of the pixels from different rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…In terms of time consumption, previous research has consistently found that a run time of ten is appropriate (Salehi et al, 2020 ). Furthermore, the standard deviation (SD) of average value is used to check the statistical property of accuracy for all ML algorithms for a robust and reliable algorithm consideration (Wang et al, 2022a , 2022b ). To report the results, Fig.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of time consumption, previous research has consistently found that a run time of ten is appropriate (Salehi et al, 2020 ). Furthermore, the standard deviation (SD) of average value is used to check the statistical property of accuracy for all ML algorithms for a robust and reliable algorithm consideration (Wang et al, 2022a , 2022b ). To report the results, Fig.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…There are a few publications that investigate sustainable logistics and supply chain management from the perspective of supply chain network partners, such as suppliers, manufacturers, and customers, as well as the perspective of the innovative and intelligent supply chain, such as internet of things (IoT), big data, AI, and blockchain technology. Furthermore, rather than using real data from businesses, many publications use the quantitative (Likert scale) or qualitative scale (Fuzzy) method to collect data (Wang et al, 2022a , 2022b ). In this study, we develop a hybrid model in which we use the data envelopment analysis (DEA) technique to enhance the predictive power of different ML of linear and nonlinear techniques (linear regression and artificial neural network (ANN)) when dealing with few data in the domain of logistics and economics (e.g., LPI, microeconomic and macroeconomic data which biannually arrangement).…”
Section: Introductionmentioning
confidence: 99%